2016
DOI: 10.1590/1807-3107bor-2016.vol30.0061
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and substantivity of Uncaria tomentosa in infected root canal dentin

Abstract: The aim of this study was to analyze the antimicrobial activity and substantivity of Uncaria tomentosa Willd DC (cat's claw, CC) in root dentin contaminated with Enterococcus faecalis. Forty-eight human premolars were contaminated with E. faecalis (ATCC 29212) and randomly divided into four groups according to the irrigant used during chemomechanical preparation (CMP): CC group: 2% CC gel; CHX group: 2% chlorhexidine digluconate gel (CHX); NaOCl group: 5.25% sodium hypochlorite (NaOCl); and SS group: sterile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…For instance, Ccahuana-Vasquez et al [5] found that micropulverized U. tomentosa inhibited Staphylococus spp but failed to inhibit P. aeruginosa while another study [40] showed that U. tomentosa gel had an inhibitory effect on Staphylococus spp but was not active towards E. faecalis , suggesting that U. tomentosa type of extract may affect bacterial inhibition [2]. However, Herrera et al [40] proved the antibacterial effect of U. tomentosa against E. faecalis in infected dentin. Our results align with these findings and evidence that antimicrobial activity varied according to U. tomentosa part, location and results suggested strain dependence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ccahuana-Vasquez et al [5] found that micropulverized U. tomentosa inhibited Staphylococus spp but failed to inhibit P. aeruginosa while another study [40] showed that U. tomentosa gel had an inhibitory effect on Staphylococus spp but was not active towards E. faecalis , suggesting that U. tomentosa type of extract may affect bacterial inhibition [2]. However, Herrera et al [40] proved the antibacterial effect of U. tomentosa against E. faecalis in infected dentin. Our results align with these findings and evidence that antimicrobial activity varied according to U. tomentosa part, location and results suggested strain dependence.…”
Section: Discussionmentioning
confidence: 99%
“…191 NaOCl is the main endodontic irrigant used, because of its antibacterial properties and ability to dissolve organic tissues. 192 CHX, usually at 2% and in a gelbased format, has been proposed as an alternative to NaOCl because of its antimicrobial activity against gram-negative and gram-positive bacteria, 191 substantivity, 193,194 and lower cytotoxicity. 195 EDTA is widely used in clinical practice since it removes the contaminated smear layer and debris formed during CMP, opening the dentinal tubules to receive an intracanal medication (ICM) or an endodontic sealer.…”
Section: Treatment Of the Endodontic Infectionmentioning
confidence: 99%
“…, Herrera et al . ). This process is known as substantivity and is claimed to be a potential advantage of CHX when used as an irrigant and intracanal medicament during root canal treatment (Khademi et al .…”
Section: Introductionmentioning
confidence: 97%